Multicomponent wound coating in treatment of an experimental, purulent wound - A. Yu. Grigoryan; A. I. Bezhin; T. A. Pankrusheva; B. S. Sukovatykh; M. S. Chekmareva; L. V. Zhilyaeva (Бюллетень сибирской медицины)
Objectives. To substantiate the effectiveness of the wound coating developed by us, which combines broad-spectrum antimicrobial effect, sorption activity, analgesic effect and prolonged action on a purulent wound.Materials and methods. The material for the study was wound coating in the form of a film developed at Kursk State Medical University (Russian patent number 2605343). Experimental animals (Wistar rats) were divided into 2 groups (comparative and experimental) of 36 animals in each. In all the experimental animals a purulent wound was modeled according to the method proposed by P.I. Tolstikh. Local anesthetic activity was determined on rabbits of the Chinchilla breed (20 individuals in each group). In the course of the study, the following methods were used: microbiological method (identification of the areas of growth retardation and wound contamination), visual assessment of the wounds, planimetric method, pH evaluation of the wounds, and Renier’s technique (for determination of the anesthetic activity). The data were processed statistically, and the statistical significance of the differences was determined using the nonparametric Mann – Whitney test. The differences were considered statistically significant at p ≤ 0.05.Results. Before the experiment on animals, high efficacy of the developed film was proven for the most common test strains of microorganisms capable of causing wound infection, using the microbiological method of investigation. Using the Renier’s method, the ability of the film to provide a local anesthetic effect was demonstrated, which was significantly higher than that of the 2% lidocaine ointment. Following visual evaluation of the wound, it was found that purification and regeneration of the wounds occurred earlier in the animals from the experimental group. The speed of wound healing in the experimental group was 1.3 times higher at 1–3 days, whereas at 5–8 days the situation was reversed in favor of the comparison group. In addition, at day 8 wound contamination in the experimental group was 1.2 times lower than in the comparison group. According to the results of the pH evaluation, significant differences between the groups were noted at days 5, 8, 15. Approximation of pH values to those of intact skin also proved the effectiveness of using the developed film.Conclusion. The results of the conducted studies confirmed broad-spectrum antimicrobial activity of the developed film, its local anesthetic activity and efficacy in treatment of experimental purulent wounds, which allows to recommend it for further preclinical trials.